Multimodal maxillofacial 3D measurement and analysis methods based on artificial intelligence and their progress - XIANG Wenzhi; CUI Weiyi; TAO Leran; YU Hongbo (Kouqiang hemian waike zazhi)
Cephalometric analysis is indispensable for orthodontic and orthognathic treatment. With the development of three-dimensional (3D) imaging technology, 3D imaging is increasingly used to assess dentomaxillofacial deformity and formulate treatment plans. 3D cephalometric analysis based on multi-modal data contains more anatomical information than traditional 2D cephalometric analysis, which can be used to conduct a more comprehensive diagnosis of patients with dentomaxillofacial deformities, and has become a research hotspot. However, its application is accompanied by the problem of time-consuming and laborious. In recent years, the emergence of artificial intelligence (AI) can assist in the automation of landmark positioning, data collection and analysis in 3D cephalometric measurement. In this article, research status and the auxiliary application of AI in 3D cephalometric analysis were reviewed and summarized.